Integrated biorefinery for bioethanol and succinic acid co-production from bread waste: techno-economic feasibility and life cycle assessment - Hafyan, Rendra Hakim; Mohanarajan, Jasmithaa; Uppal, Manaal; Kumar, Vinod; Narisetty, Vivek; Maity, Sunil K.; Sadhukhan, Jhuma; Gadkari, Siddharth (Elsevier, 2024)
In this study, an advanced decarbonization approach is presented for an integrated biorefinery that co-produces bioethanol and succinic acid (SA) from bread waste (BW). The economic viability and the environmental performance of the proposed BW processing biorefinery is evaluated. Four distinctive scenarios were designed and analysed, focusing on a plant capacity that processes 100 metric tons (MT) of BW daily. These scenarios encompass: (1) the fermentation of BW into bioethanol, paired with heat and electricity co-generation from stillage, (2) an energy-optimized integration of Scenario 1 using pinch technology, (3) the co-production of bioethanol and SA by exclusively utilizing fermentative CO2, and (4) an advanced version of Scenario 3 that incorporates carbon capture (CC) from flue gas, amplifying SA production. Scenarios 3 and 4 were found to be economically more attractive with better environmental performance due to the co-production of SA. Particularly, Scenario 4 emerged as superior, showcasing a payback period of 2.2 years, a robust internal rate of return (33% after tax), a return on investment of 32%, and a remarkable net present value of 163 M$. Sensitivity analysis underscored the decisive influence of fixed capital investment and product pricing on economic outcomes. In terms of environmental impact, Scenario 4 outperformed other scenarios across all impact categories, where global warming potential, abiotic depletion (fossil fuels), and human toxicity potential were the most influential impact categories (−0.344 kg CO2-eq, −16.2 MJ, and −0.3 kg 1,4-dichlorobenzene (DB)-eq, respectively). Evidently, the integration of CC unit to flue gas in Scenario 4 substantially enhances both economic returns and environmental sustainability of the biorefinery.
Keywords: Bread waste valorisation; Techno-economic analysis; Life cycle assessment; Carbon capture; Bioethanol; Succinic acid